Karakteristik fisik selulosa dari rumput laut Chaetomorpha crassa yang diekstraksi dengan suhu yang berbeda: Physical characteristics of cellulose from seaweed Chaetomorpha crassa extracted at different temperatures - Henggu, Krisman Umbu; Jodi, Jasin Umbu; Ratu, Oksin Hama; Sihono, Sihono; Nurdiansyah, Yopi (Jurnal Pengolahan Hasil Perikanan Indonesia, 2024)
Chaetomorpha crassa is a green seaweed that is abundant in Indonesian waters. The utilization of C. crassa is yet to be fully optimized, as seaweed farmers often view it as a nuisance. However, this seaweed contains natural cellulose, which can be used in industrial applications. Consequently, this study aims to determine the optimal temperature for cellulose extraction from C. crassa, focusing on cellulose content, physical characteristics, and diffraction patterns. The cellulose extraction process involves several stages: depigmentation and delignification at extraction temperatures of 60, 70, and 80°C for 12 h, followed by depolymerization using 5% HCl. The biomass was dried at 60°C for 10 h. The parameters analyzed included the degree of crystallinity, density, flowability index, and porosity, as well as the cellulose, lignin, hemicellulose content, and diffraction patterns. The findings indicated that variations in extraction temperatures of 60°C, 70°C, and 80°C significantly affected (p<0.05) the cellulose, lignin, hemicellulose, bulk density, tap density, Carr's index, Hausner ratio, and porosity. The optimal conditions for cellulose extraction were achieved at a temperature of 70°C, resulting in an average cellulose content of 74.17%, a degree of crystallinity of 64.13%, bulk density of 0.21 g/cm³, tap density of 0.29 g/cm³, Carr's index of 35.11%, Hausner ratio of 2.48, and porosity of 1.27. Diffraction analysis revealed that the cellulose obtained in this study was predominantly type II cellulose (72.66%), with type I cellulose comprising 27.34%.